Attitudes of Hungarian young consumers towards mobile marketing - Somogyi, Ildikó; Bányai, Edit (The Hungarian Journal of Marketing and Management, 2019)
This study summarizes the different approaches of mobile marketing and advertising and explores the situation of mobile marketing in Hungary. The consumer attitudes towards mobile advertising are also examined, primarily focused on the Hungarian young generation between the age of 18-30, in which group a questionnaire based research was conducted in October 2008. The survey shows that the fundamental conditions of mobile marketing and advertising are given in Hungary but the majority of young consumers do not use the required mobile functions, which transmit the mobile ads. Their attitude towards mobile marketing and advertising depends on their mobile usage habits.